(untitled) (Global Journal of Medical Research, 2023)
From ancient times cow pee has been utilised to treat a variety of human illnesses It is a crucial and integral component of Panchgavya Chikitsa Ayurveda classics have emphasised its value and usage in treatments such decoction purgation and enema for the treatment of Kushtha vitiligo Kandu eczema Udarrog disorders of GI track colic abdominal tumours cancer treatment enlargement of the belly and flatulence etc Numerous studies have also been conducted that demonstrate the effectiveness of this substance in treating a variety of conditions including those related to the skin the stomach the kidneys the heart the liver stones diabetes athletes foot cysts haemorrhoids and the liver as well as its immunostimulant bioenhancer anticonvulsant anticancer wound-healing antioxidant and antimicrobial properties It may be used in agriculture to make bio insecticides and vermin compost The distillate of cow urine which is a good bio enhancer just received U S patent protection To demonstrate its traits and advantages further study is needed